FoxO1 inhibits autophagosome-lysosome fusion leading to endothelial autophagic-apoptosis in diabetes. Issue 14 (23rd January 2019) - Zhang, Hui; Ge, Song; He, Kesuai; Zhao, Xin; Wu, Ya; Shao, Yongfeng; Wu, Xiaohong
Abstract: Aims: Inadequate autophagy contributed to endothelial dysfunction in diabetic patients. We aimed to investigate the relationship between inadequate autophagy and endothelial cells (ECs) apoptosis in diabetes and its underlying mechanism. Methods and results: Aortic intima and ECs were isolated from diabetic patients. Cultured human aortic endothelial cells (HAECs) were stimulated with advanced glycation end products (AGEs). The expression of autophagy and apoptosis-related proteins were determined by western blotting. Autophagosomes were observed by electron microscopy. The fusion of autophagosome and lysosomes was detected by immunofluorescence. Compared with non-diabetic subjects, the levels of LC3-II, p62, FoxO1, and Ac-FoxO1 were increased in ECs from diabetic patients, accompanied by the decreased expressions of Atg14, STX17, and co-localization of LC3-II/LAMP2 and Atg14/STX17. Long-term stimulation with AGEs up-regulated LC3-II and p62 expression and the number of autophagosomes with decreased level of Atg14, STX17, Ras-related protein 7 (Rab7), and co-localization of LC3-II/LAMP2 and Atg14/STX17 in HAECs. The apoptosis rates were increased with elevated cleaved-caspase-3 and declined Bcl-2 expression. Inhibition of autophagy with 3-methyladenine could reduce long-term AGEs-induced apoptosis. Higher levels of FoxO1, Ac-FoxO1, and Ac-FoxO1 binding to Atg7 were detected in AGEs-treated HAECs. AGEs-induced FoxO1 enhanced Akt activity, decreased SIRT1-deacetylase activity by phosphorylation and elevated Ac-FoxO1. Knockout of FoxO1 reduced AGEs-induced autophagy and promoted the expression of Atg14 and the co-localization of LC3-II/LAMP 2 and Atg14/STX17. Conclusion: Inadequate autophagy with impaired autophagosome-lysosomal fusion exists in aortic intima and ECs from diabetic patients. FoxO1 mediates AGEs-induced ECs autophagic apoptosis through impairing autophagosome-lysosomes fusion by inhibiting Atg14 expression.